Implementation of the Use of Google Classroom for Statistics Courses for Islamic Religious Education Students at Wiralodra University Indramayu in 2023/2024 - Wahyu Aji; Mar’atus Sholiha (Konsultan Jurnal Ilmiah Indonesia, 2025)
The purpose of this research is to find out how to implement the use of Google Classroom in statistics courses for Islamic Religion Education students at Wiralodra University. This research uses qualitative methods with qualitative descriptive techniques, because research is by collecting data according to the truth and then the data is compiled, processed, and analyzed to be able to provide an accurate picture of the problem being discussed. When Indonesia was hit by Covid-19, various efforts were made by the government to overcame Covid-19, then the government issued policies such as PPKM (Implementation of Restrictions on Community Activities), so all activities could only be carried out online including learning activities at unoersities carried out online. One of the learning media used by students in online learning is Google Classroom, even ow there are still several universities that still use Google Classroom learning media because it is easy and time is flexible.